1999
DOI: 10.2337/diabetes.48.9.1686
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the docked granule pool responsible for the first phase of glucose-stimulated insulin secretion.

Abstract: The mechanisms underlying the first phase of glucose-stimulated insulin release, the deterioration of which marks the early stages of both type 1 and type 2 diabetes, are essentially unknown. Among many hypotheses, one holds that the first phase is due to a readily releasable pool of insulin-containing granules. We used current knowledge of the mechanisms of exocytosis and the proteins involved in docking granules at the plasma membrane to test this hypothesis. A docked pool of readily releasable granules was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(157 citation statements)
references
References 13 publications
7
145
1
4
Order By: Relevance
“…Also, human β-cell-exocytosis does not plateau for depolarizations up to 500 ms (Braun et al, , 2009, again arguing against pool depletion. However, this does not means that depletion of the RRP is irrelevant for biphasic insulin secretion, indeed there is good evidence for a role of a finite pool of granules (Daniel et al, 1999;Henquin et al, 2002;Olofsson et al, 2002), but rather that short depolarizations of increasing lengths do not show evidence of a smaller IRP. Finally, our results confirmed that cAMP-raising agents such as forskolin increase the efficacy of Ca 2+ on exocytosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, human β-cell-exocytosis does not plateau for depolarizations up to 500 ms (Braun et al, , 2009, again arguing against pool depletion. However, this does not means that depletion of the RRP is irrelevant for biphasic insulin secretion, indeed there is good evidence for a role of a finite pool of granules (Daniel et al, 1999;Henquin et al, 2002;Olofsson et al, 2002), but rather that short depolarizations of increasing lengths do not show evidence of a smaller IRP. Finally, our results confirmed that cAMP-raising agents such as forskolin increase the efficacy of Ca 2+ on exocytosis.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of the granules belong to a reserve pool (RP) and these needs to be transported, docked and primed prior to release. On a cellular level it has been suggested that first phase insulin secretion is equivalent to release of granules from the IRP/RRP and second phase insulin secretion correspond to the release of granules from the RP (Daniel et al, 1999;Eliasson et al, 2008). Interestingly, first phase insulin secretion is lacking in patients with type 2 diabetes (Hosker et al, 1989) why studies investigating the control of the IRP/RRP is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…This pool of insulin granules has been referred as the readily releasable pool, and it appears to account for the first phase of stimulusmediated insulin secretion (13). This initial release process requires the functional interactions of the t-SNARE 1 proteins, syntaxin 1 and SNAP25, with the v-SNARE protein, VAMP2.…”
mentioning
confidence: 99%
“…Glucagon release was measured under perifusion condition (Kikuchi et al, 1974;Daniel et al, 1999). Forskolin (10 |oM) enhanced the effect of AVP (100 riM) on glucagon release (a peak of -3 fold and -7 fold of the baseline level for AVP and the combination of AVP and forskolin, respectively) (Fig.…”
Section: Enhancement By Forskolin Of a Vp-induced Glucagon Release Frmentioning
confidence: 99%
“…Glucagon release was measured under perifusion condition as previously described (Kikuchi et al, 1974;Daniel et al, 1999). Briefly, InRlG9 cells were grown in custommade coverslips, which were placed in a perifusion chamber.…”
Section: Perifusion Of Inrlg9 Cellsmentioning
confidence: 99%